2012
DOI: 10.1136/annrheumdis-2011-201201
|View full text |Cite
|
Sign up to set email alerts
|

Identifying core domains to assess flare in rheumatoid arthritis: an OMERACT international patient and provider combined Delphi consensus

Abstract: As part of the process to develop a measure for RA flare, patients and HCPs agreed on eight core domains. Next steps include identifying items to assess domains and conducting studies to validate and refine a new measure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
110
0
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 132 publications
(115 citation statements)
references
References 25 publications
3
110
0
2
Order By: Relevance
“…This analysis was only performed for the primary working definition of flare, based on patient-reported worsening. The sequence for addition of variables was guided by the results from the final Delphi exercise held by the OMERACT RA Flare Group (variable for domain with highest agreement added first),7 and in cases in which more than one variable per domain was available, the variable yielding the highest SMD between patients with and without flare was selected. The analyses were first performed in all patients (with the stiffness variable added last due to missing data) and then in patients with available stiffness data.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…This analysis was only performed for the primary working definition of flare, based on patient-reported worsening. The sequence for addition of variables was guided by the results from the final Delphi exercise held by the OMERACT RA Flare Group (variable for domain with highest agreement added first),7 and in cases in which more than one variable per domain was available, the variable yielding the highest SMD between patients with and without flare was selected. The analyses were first performed in all patients (with the stiffness variable added last due to missing data) and then in patients with available stiffness data.…”
Section: Methodsmentioning
confidence: 99%
“…Through a process involving dedicated patient focus groups in five countries and three rounds of Delphi exercises with both healthcare professionals (HCPs) and patients with RA participating, a set of 14 candidate domains for flare were identified—pain, tender joints, swollen joints, physical function, patient global assessment, physician global assessment, laboratory measures, fatigue, stiffness, participation, self-management, systemic features, sleep and emotional distress 5 7. The latter six domains are not part of the core set for assessment of RA,8 9 while fatigue was identified by OMERACT patients as important to assess and has been included in the most recent recommendations on reporting of disease activity in clinical trials 10 11.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…When comparing these outcomes to the ones in this study, there is a high degree of overlap. This is a somewhat surprising result, since other researchers that included both patient and HCP perspective in their research pertaining to chronic diseases have reported marked discrepancies in the two perspectives [28][29][30]. There was one clear exception to this high agreement between patients and HCPs: depression.…”
Section: Discussionmentioning
confidence: 41%
“…While not yet validated, such a definition is being developed using Outcome Measures in Rheumatology Clinical Trials RA flare criteria 19 . Fifth, studies should be designed to have enough power to create statistical models to detect important predictors of successful withdrawal, such as age, sex, and type of background RA therapy.…”
Section: Rheumatologymentioning
confidence: 99%